Application of the Recitation Method in the Presentation of the Qur'an Hadith in Class X A Madrasah Aliyah Waburense, Central Buton Regency - Junudin, Maya; Rahim, Abdul; Darmayanti, Darmayanti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the implementation of the recitation method in the learning of Qur’an and Hdith subjects in Grade X A of Madrasah Aliyah Waburense and to evaluate its effectiveness in enhancing students, which they must complete and present independently outside of class time. This research uses a qualitative approach with data collected trough observation, interviews, and documentation. The results show that the implementation of the recitation method increases student engagement in the learning process, strengthens understanding of Qur’an and Hadith material, and fosters responsibility and independent learning attitudes. Challenges encountered include time constraints and varying student abilities in completing assignments. Overall, the recitation method has proven to be quite effective and relevant for Qur’an and Hadith learning in Madrasah Aliyah.